2014
DOI: 10.1038/srep04986
|View full text |Cite
|
Sign up to set email alerts
|

The pseudoginsenoside F11 ameliorates cisplatin-induced nephrotoxicity without compromising its anti-tumor activity in vivo

Abstract: The clinical use of cisplatin was severely limited by its associated nephrotoxicity. In this study, we investigated whether the pseudoginsenoside F11 had protective effects against cisplatin-induced nephrotoxicity. To clarify it, one in vivo model of cisplatin-induced acute renal failure was performed. The results showed that pretreatment with F11 reduced cisplatin-elevated blood urea nitrogen and creatinine levels, as well as ameliorated the histophathological damage. Further studies showed that F11 could sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
1
17
1
Order By: Relevance
“…Cisplatin (CP) is a well-known antineoplastic drug extensively used for treatment of different solid tumors, such as cervical, ovarian cancer and testicular cancer ( 1 , 2 ). However, it has been observed that CP accumulates in the kidney with a greater degree than other organs and so renal damage is the major dose- limiting side effect of this drug ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin (CP) is a well-known antineoplastic drug extensively used for treatment of different solid tumors, such as cervical, ovarian cancer and testicular cancer ( 1 , 2 ). However, it has been observed that CP accumulates in the kidney with a greater degree than other organs and so renal damage is the major dose- limiting side effect of this drug ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their particular structure not having a heat-labile C-20 glycoside, these saponins were gradually degraded to ocotillol genin, which exhibited the kidney cell protective effect in the in vitro model. Moreover, pseudoginsenoside F11, a minor ocotillol-type saponin in Panax ginseng, was reported to have a protective effect against cisplatin-induced acute renal failure in an in vivo model [30]. These findings could be explained by a study by Jeong et al, which described the metabolism of these saponins to ocotillol genin by gut microbiota in a human faecal suspension [39].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the kidney cell protective effect increased gradually with the increase of time and reached a maximum at 12 h. Most of the less polar saponins possessing the kidney cell protective effect are protopanaxadiol-type saponins, including G-Rg3, -Rk1, -Rg5, -Rh2, and -Rh3 [22,[35][36][37]. Only a few studies of the kidney protective effect of protopanaxatriol-type saponins (G-Rk3 and -Rh4) and ocotillol-type saponins (pseudoginsenoside F11) have been reported [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lewis lung cancer cell xenograft tumors were established in C57BL/6 mice as previously reported 33 . When the tumors had grown to 200–300 mm 3 , the mice were randomly assigned to 4 groups (n = 13 each).…”
Section: Methodsmentioning
confidence: 99%